PENGARUH IMPLEMENTASI CORETAX SYSTEM TERHADAP TRANSPARANSI DAN AKUNTABILITAS WAJIB PAJAK - Gusna Ratna Puspita; Dini Aryani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the impact of implementing the Coretax System on the accountability and transparency of taxpayers. Utilizing a quantitative approach with a survey method, data were gathered from 50 taxpayer respondents selected through random sampling. Data analysis was performed using simple linear regression technique with IBM SPSS version 25 software. The research findings indicate that the standardization of the Coretax System contributes positively and significantly to taxpayer transparency (regression coefficient = 0.720; tstatistic = 16.693; sig. = 0.000). A positive and significant effect was also found on the accountability variable (regression coefficient = 0.653; tstatistic = 12.238; sig. = 0.000). Based on the coefficient of determination test, this system contributes 85.3% to transparency and 75.7% to accountability. Overall, the integration of the Coretax System is proven effective in strengthening information disclosure while fostering a sense of responsibility among taxpayers in complying with fiscal regulations.